Vitamin D level in children with type 1 diabetes in Misrata, Libya - Ftattet, Naima H.; Trish, Eiman O.; Badi, Aya E.; Alkobti, Hajer H. (Scientific Journal for Faculty of Science-Sirte University, 2024)
Vitamin D deficiency can contribute to the pathogenesis of many autoimmune diseases, including type 1 diabetes. Therefore, this study aimed to determine the relationship between vitamin D deficiency and type 1 diabetes and some factors related to it. The study was conducted on 100 children with diabetes and 40 non-diabetic children from the city of Misurata. Samples were collected by using a questionnaire over a period of 4 months. The study showed a significant relationship (P-value <0.05) between the level of vitamin D and patients with type 1 diabetes. The percentage of vitamin D deficiency in sick children was higher compared to healthy children (59%) (55%), respectively, and the percentage of vitamin D deficiency did not constitute and its relationship to age, gender, residential area, duration of exposure to the sunlight, and seasons of the year, showed statistical significance (P-value > 0.05), and the most age groups suffering from vitamin D deficiency were those between the ages of (11-16 years) in patients and healthy people, The rate of vitamin D deficiency was higher in females than in males. The percentage of vitamin D deficiency and taking supplements was statistically significant, and there was an inverse relationship between fasting blood sugar and vitamin D levels. The percentage of vitamin D deficiency duration of diabetes, and HbA1c did not constitute any statistical significance. This current study concluded that vitamin D deficiency is common in children, whether in patients or healthy people.